Problematika Pesantren dan Lembaga Pendidikan Islam - Hening Puwati Parlan; Andriyani; Nurmalia Lusida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Islamic boarding schools and educational institutions play an important role in maintaining and passing on Islamic religious values, culture, and traditional values. They also play an important role in shaping the character, morals and spirituality of society. However, they face many challenges in the complex modern world. This research investigates the problems faced by Pesantren and Islamic education institutions in Indonesia. It does so by using a qualitative approach and descriptive analysis. The study shows that Pesantren greatly help overcome poverty, strengthen brotherhood, lower unemployment rates, and combat ignorance. However, they also face many challenges, such as the dynamics of modernization and globalization that often conflict with their traditional values, limited resources and infrastructure, and the difficulty of integrating modern education curriculum with traditional religious education. Pesantren have a strategic position to address social issues, but they face problems such as limited resources and curriculum integration. Curriculum improvements and enhanced educational methodologies are needed to achieve this. Pesantren should increase general subjects, strengthen research activities, improve soft skills, and cooperate with other educational institutions.